2013
DOI: 10.1007/s00417-013-2464-7
|View full text |Cite
|
Sign up to set email alerts
|

Global rates of glaucoma surgery

Abstract: There is a paucity of data on rates of glaucoma surgery, particularly from developing countries. The new metric GSR may be useful for the allocation of healthcare resources, as well as for planning and monitoring public health interventions in glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 28 publications
2
35
1
Order By: Relevance
“…However, trabeculectomy was the most commonly performed glaucoma surgery in France during this 10-year period. This is in agreement with a recent study reporting that trabeculectomy was the most frequently performed glaucoma surgery in 21 countries 13. Ciliary body destruction gained more acceptance among French ophthalmologists with a 73% increase over this observation period.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…However, trabeculectomy was the most commonly performed glaucoma surgery in France during this 10-year period. This is in agreement with a recent study reporting that trabeculectomy was the most frequently performed glaucoma surgery in 21 countries 13. Ciliary body destruction gained more acceptance among French ophthalmologists with a 73% increase over this observation period.…”
Section: Discussionsupporting
confidence: 92%
“…This huge difference may account for different treatment modalities available in a given region, the level of reimbursement for patients and may depend on the number of ophthalmologists in a given area. In this study, we observed a positive association between the number of operating room-based glaucoma procedures and the number of ophthalmologists only for the country's 14 regions, in agreement with a recent report 13. Even though all ophthalmologists do not perform surgery, at least in France, non-surgical colleagues refer their patients with glaucoma to glaucoma surgeons when a surgical procedure is needed.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations